2005
DOI: 10.1007/s10734-004-6349-x
|View full text |Cite
|
Sign up to set email alerts
|

Communication in an academic context

Abstract: The purpose of this qualitative case study is to investigate the most common communication problems from the views of faculty members at the Middle East Technical University in Ankara, Turkey. The sample of this study consists of 50 faculty members including professors, associate professors, assistant professors, and instructors from five largest departments representing five colleges at the Middle East Technical University. The data were gathered by utilizing interview method, including 19 interview questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 27 publications
1
20
0
3
Order By: Relevance
“…It appeared in Case 'A' that academics also believed that they should deliver their subject in their own way. This finding is consistent with Gizir and Simsek (2005) who found that each discipline of knowledge has its own set of concepts, methods and fundamental aims, and that academics have a distinctive culture that includes attitudes, activities and cognitive style. Therefore, as the faculty's QMS stated the way that subjects should be taught, individualism was seen as working against ISO 9001 maintenance activities.…”
Section: The Influence Of Individualism On Iso 9001 Maintenance Activsupporting
confidence: 90%
“…It appeared in Case 'A' that academics also believed that they should deliver their subject in their own way. This finding is consistent with Gizir and Simsek (2005) who found that each discipline of knowledge has its own set of concepts, methods and fundamental aims, and that academics have a distinctive culture that includes attitudes, activities and cognitive style. Therefore, as the faculty's QMS stated the way that subjects should be taught, individualism was seen as working against ISO 9001 maintenance activities.…”
Section: The Influence Of Individualism On Iso 9001 Maintenance Activsupporting
confidence: 90%
“…Many writers, including ourselves, have described university teaching as a solitary business (Ramsden 1998;Handal 1999;Roxå and Mårtensson 2004;Gizir and Simsek 2005). Becher and Trowler (2001) describe the seemingly contradictory nature of communication in academia.…”
Section: Academic Communicationmentioning
confidence: 99%
“…The uses of disciplinary cultures as an intellectual device, however, vary significantly. Disciplinary cultures may be used as one of the structuring principles in the study, essential for the analysis of the empirical data (see Gizir and Simsek 2005;Kekäle 2000;Quinlan and Åkerlind 2000;Ylijoki 2000Ylijoki , 2003. These studies may also discuss and develop cultural studies on higher education through introducing new concepts -like departmental cultureto be utilized in the analysis (Quinlan and Åkerlind 2000).…”
Section: Disciplinary Culturesmentioning
confidence: 99%